Comparison of estimated anterior cruciate ligament tension during a typical and flexed knee and hip drop landing using sagittal plane knee modeling - Southard, J.; Kernozek, T. W.; Ragan, R.; Willson, J. (International Journal of Sports Medicine, 2012)
Noncontact mechanisms, such as landing from a jump, account for over 70% of all anterior cruciate ligament injuries. Increased knee and hip flexion during landing has been suggested to decrease anterior cruciate ligament tension; however, current literature utilizing knee modeling approaches has not investigated this. Our purpose was to compare estimated anterior cruciate ligament tension in females between a typical and flexed knee and hip drop landing performance. A sagittal plane knee model based on kinematic, kinetic, electromyography, and cadaveric data was used to estimate forces on the anterior cruciate ligament during a typical and flexed drop landing for 23 females. Model estimated peak anterior cruciate ligament tension decreased by 10% during the flexed landing performance (p=0.008). This was accounted for by an increase in hamstring shear force by 6% of body weight and a reduction in patellar tendon shear force and femur-tibia shear force by 3% of body weight each. Results suggest that simple verbal cues for increased knee and hip flexion during landing may be effective in reducing anterior cruciate ligament tension and potential risk of injury during landing.